Giant coronary artery aneurysm of the left main treated with a covered stent: a case report. Issue 1 (7th December 2022) - Holvoet, Wouter; van den Buijs, Deborah; Bogaerts, Eline; Willems, Endry; Ameloot, Koen; Dens, Jo
Abstract: Background: Coronary artery aneurysms (CAAs) of the left main represent a small subset of coronary artery disease and are associated with cardiovascular death. Because of its rare entity, large data are lacking and therefore treatment guidelines are missing. Case summary: We describe a case of a 56-year-old female with a past medical history of spontaneous dissection of the distal descending left artery (LAD) 6 years before. She presented to our hospital with a non-ST elevation myocardial infarction and a coronary angiogram showed a giant saccular aneurysm of the shaft of the left main coronary artery (LMCA). Given the risk of rupture and distal embolization, the heart team decided to go for a percutaneous approach. Based on a pre-interventional 3D reconstructed CT scan and guided by intravascular ultrasound, the aneurysm was successfully excluded with a 5 mm papyrus-covered stent. At 3-month and 1-year follow-up, the patient is still asymptomatic and repeat angiographies showed full exclusion of the aneurysm and the absence of restenosis in the covered stent. Discussion: We describe the successful percutaneous IVUS-guided treatment of a giant LMCA shaft coronary aneurysm with a papyrus-covered stent with an excellent 1-year angiographic follow-up showing no residual filling of the aneurysm and no stent restenosis. Video Abstract: